THE EFFECTIVENESS OF CELERY BOILED WATER ON LOWERING BLOOD PRESSURE IN THE ELDERLY WITH HYPERTENSION IN THE WORKING AREA OF THE SIMALINGKAR PUBLIC HEALTH CENTER IN 2020 - Lasria Simamora; Ninsah M.P Br. Sembiring; Asnita Sinaga (International Journal of Midwifery Research, 2022)
Hypertension or high blood pressure is an increase in systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg on two measurements with an interval of five minutes in a rest/quiet state. The management of hypertension can basically be done pharmacologically and non-pharmacologically. One non-pharmacological treatment is to use celery. Celery contains the flavonoid apigenin, vitamin C, apiin, calcium, and magnesium which can reduce hypertension. This study aims to analyze the effectiveness of celery boiled water in lowering blood pressure in patients with hypertension. This study used a pre post experimental design. The number of respondents at the Simalingkar Health Center workplace as many as 20 respondents who were given celery boiled water with a significance level of <0.05. The results showed that the P value of 0.00 (<0.05) means that celery boiled water is effective in reducing systolic and diastolic blood pressure in hypertensive patients. The average difference between systolic and diastolic after drinking celery boiled water found an average difference between systolic and diastolic 15 mmHg and 10 mmHg, so it can be concluded that celery boiled water is effective for reducing hypertension.